On the Asymptotic Behavior of Solutions of Linear Differential Equations - Nguyen Minh Man; Nguyen The Hoan (Український математичний журнал, 2003)
We present sufficient conditions for the linear asymptotic equilibrium of linear differential equations in Hilbert and Banach spaces. The results obtained are applied to studying the asymptotic equivalence of two linear differential equations.